Inhibition of MicroRNA-146a and Overexpression of Its Target Dihydrolipoyl Succinyltransferase Protect Against Pressure Overload-Induced Cardiac Hypertrophy and Dysfunction. Issue 8 (22nd August 2017) - Heggermont, Ward A.; Papageorgiou, Anna-Pia; Quaegebeur, Annelies; Deckx, Sophie; Carai, Paolo; Verhesen, Wouter; Eelen, Guy; Schoors, Sandra; van Leeuwen, Rick; Alekseev, Sergey; Elzenaar, Ies; Vinckier, Stefan; et al.
Abstract : Background: Cardiovascular diseases remain the predominant cause of death worldwide, with the prevalence of heart failure continuing to increase. Despite increased knowledge of the metabolic alterations that occur in heart failure, novel therapies to treat the observed metabolic disturbances are still lacking. Methods: Mice were subjected to pressure overload by means of angiotensin-II infusion or transversal aortic constriction. MicroRNA-146a was either genetically or pharmacologically knocked out or genetically overexpressed in cardiomyocytes. Furthermore, overexpression of dihydrolipoyl succinyltransferase (DLST) in the murine heart was performed by means of an adeno-associated virus. Results: MicroRNA-146a was upregulated in whole heart tissue in multiple murine pressure overload models. Also, microRNA-146a levels were moderately increased in left ventricular biopsies of patients with aortic stenosis. Overexpression of microRNA-146a in cardiomyocytes provoked cardiac hypertrophy and left ventricular dysfunction in vivo, whereas genetic knockdown or pharmacological blockade of microRNA-146a blunted the hypertrophic response and attenuated cardiac dysfunction in vivo. Mechanistically, microRNA-146a reduced its target DLST—the E2 subcomponent of the α-ketoglutarate dehydrogenase complex, a rate-controlling tricarboxylic acid cycle enzyme. DLST protein levels significantly decreased on pressure overload in wild-type mice, paralleling a decreased oxidative metabolism, whereas DLST protein levels and hence oxidative metabolism were partially maintained in microRNA-146a knockout mice. Moreover, overexpression of DLST in wild-type mice protected against cardiac hypertrophy and dysfunction in vivo. Conclusions: Altogether we show that the microRNA-146a and its target DLST are important metabolic players in left ventricular dysfunction. Abstract : Supplemental Digital Content is available in the text.